2022
DOI: 10.3390/antiox11020413
|View full text |Cite
|
Sign up to set email alerts
|

Can Antioxidants Reduce the Toxicity of Bisphenol?

Abstract: BPA is still the subject of extensive research due to its widespread use, despite its significant toxicity resulting not only from its negative impact on the endocrine system but also from disrupting the organism’s oxidative homeostasis. At the molecular level, bisphenol A (BPA) causes an increased production of ROS and hence a change in the redox balance, mitochondrial dysfunction, and modulation of cell signaling pathways. Importantly, these changes accumulate in animals and humans, and BPA toxicity may be a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 158 publications
(178 reference statements)
2
6
0
Order By: Relevance
“…Because bisphenols do not produce a monotonic response [61], the VitE effects depend, among other factors, on the quantity of lipids in the body. We agree with M ączka et al (2022), who mention that it is necessary to account for the influence of bisphenols on the metabolism and the power of doses of antioxidants used to attenuate their harmful effects [14]. Although there is limited information about the impact of antioxidants on BPS effects, our results support the results that indicate that BPA toxicity may be aggravated by metabolic disorders and coexisting diseases [14].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Because bisphenols do not produce a monotonic response [61], the VitE effects depend, among other factors, on the quantity of lipids in the body. We agree with M ączka et al (2022), who mention that it is necessary to account for the influence of bisphenols on the metabolism and the power of doses of antioxidants used to attenuate their harmful effects [14]. Although there is limited information about the impact of antioxidants on BPS effects, our results support the results that indicate that BPA toxicity may be aggravated by metabolic disorders and coexisting diseases [14].…”
Section: Discussionsupporting
confidence: 92%
“…We agree with M ączka et al (2022), who mention that it is necessary to account for the influence of bisphenols on the metabolism and the power of doses of antioxidants used to attenuate their harmful effects [14]. Although there is limited information about the impact of antioxidants on BPS effects, our results support the results that indicate that BPA toxicity may be aggravated by metabolic disorders and coexisting diseases [14]. However, a gap remains to be investigated between the roles of the coadministration of VitE with BPS in the pathogenesis of DM.…”
Section: Discussionsupporting
confidence: 91%
“…Another clinical application of melatonin may be environmental toxicity. Melatonin may be one of the many antioxidants to help mitigate oxidative stress from human exposure to toxicants such as bisphenol A [ 177 ]. However, much more research is needed to understand how melatonin provides benefit relative to other antioxidants.…”
Section: Clinical Usesmentioning
confidence: 99%
“…Accordingly, some authors sustained the bene cial effect of MEL on BPA -treated -rats by increased antioxidant enzymes activity (SOD, CAT, ascorbate peroxidase, Px), and by attenuated brain apoptosis (normalized p53, p53 upregulated modulator of apoptosis (PUMA), and dynamin-related protein 1 (Drp-1) expression), both at the transcriptional and translational levels (Ishtiaq 2021;Mączka 2022). Apart from these mechanisms, the MEL`s antioxidant -receptor -dependent mechanisms, have also been also mentioned (Hardeland, 2019;Xia 2012).…”
Section: Discussionmentioning
confidence: 95%
“…In our study, MEL II diminished lipid peroxidation in the hippocampus, whereas, MEL I exerted protective effects in frontal lobe of the BPA -treated rats, data which are comparable with other reports. Mączka et al, (2022) reported the e ciency of antioxidants, such as, curcumin, lycopene, luteolin and melatonin on various organs (liver, lungs, brain, and prostate) by modulation of the ROS, mitochondrial dysfunction and cell signaling pathways. The positive impact of MEL as an antioxidant has been deeply documented in the literature.…”
Section: Discussionmentioning
confidence: 99%